'The tabloid test': a qualitative interview study on the function and purpose of termination of pregnancy review committees in Victoria, Australia - Bowman-Smart, H; Keogh, L; Haining, CM; O'Rourke, A; de Crespigny, L; Savulescu, J (BioMed Central, 2023)
Background: Termination of pregnancy (TOP) is not an uncommon procedure. Availability varies greatly between jurisdictions; however, additional institutional processes beyond legislation can also impact care and service delivery. This study serves to examine the role institutional processes can play in the delivery of TOP services, in a jurisdiction where TOP is lawful at all gestations (Victoria, Australia). As per the Abortion Law Reform Act 2008, TOPs post-24 weeks require the approval of two medical practitioners. However, in Victoria, hospitals that offer post-24 week TOPs generally require these cases to additionally go before a termination review committee for assessment prior to the service being provided. These committees are not stipulated in legislation. Information about these committees and how they operate is scarce and there is minimal information available to the public.